2016
DOI: 10.1037/pspa0000055
|View full text |Cite
|
Sign up to set email alerts
|

How taking photos increases enjoyment of experiences.

Abstract: Experiences are vital to the lives and well-being of people; hence, understanding the factors that amplify or dampen enjoyment of experiences is important. One such factor is photo-taking, which has gone unexamined by prior research even as it has become ubiquitous. We identify engagement as a relevant process that influences whether photo-taking will increase or decrease enjoyment. Across 3 field and 6 lab experiments, we find that taking photos enhances enjoyment of positive experiences across a range of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
114
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 25 publications
2
114
0
3
Order By: Relevance
“…Research has shown that even unpleasant tasks (e.g., shocking yourself) are more enjoyable than doing nothing at all (Wilson et al, ). Therefore, adding a mildly enjoyable activity such as taking pictures may increase engagement and increase enjoyment of the experience, as Diehl et al () found.…”
Section: Conceptual Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Research has shown that even unpleasant tasks (e.g., shocking yourself) are more enjoyable than doing nothing at all (Wilson et al, ). Therefore, adding a mildly enjoyable activity such as taking pictures may increase engagement and increase enjoyment of the experience, as Diehl et al () found.…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…Careful inspection of the experiences studied by Diehl et al () reveals a possible resolution: All but one of their studies demonstrating a positive effect of photography on enjoyment involved an experience that was moderately enjoyable (e.g., a meal at a food court and a museum visit). Thus, Diehl et al’s () studies involved a comparison of taking pictures versus not, for moderately enjoyable experiences; their studies did not involve highly enjoyable experiences. In contrast, the experiences described by the press as being harmed by picture taking were highly enjoyable or meaningful: For example, people attending concerts by their favorite bands or parents watching their children perform.…”
Section: Conceptual Developmentmentioning
confidence: 99%
See 3 more Smart Citations